Microbial dysbiosis in periodontitis and peri-implantitis: pathogenesis, immune responses, and therapeutic - Cui, Ziwei; Wang, Peng; Gao, Weiyue (Frontiers in Cellular and Infection Microbiology, 2025)
The oral microbiome comprises over 700 distinct species, forming complex biofilms essential for maintaining oral and systemic health. When the microbial homeostasis in the periodontium is disrupted, pathogens within the biofilm can cause periodontitis and peri-implantitis, inducing host immune responses. Understanding the role of microbial communities and the immune mechanisms in oral health and disease is crucial for developing improved preventive, diagnostic and therapeutic strategies. However, many questions remain about how changes in bacterial populations contribute to the development and progression of these conditions. An electronic and manual literature search was conducted using PubMed, Excerpta Medica, Frontiers Reports and the Wiley Online Library databases for relevant articles. Data from these publications were extracted and the overall findings were summarized in a narrative manner. The variations in microbial communities and immune responses of periodontitis and peri-implantitis are explored. Dysbiosis of the subgingival microbiome—characterized by an increase in pathogenic bacteria such as Porphyromonas gingivalis, Tannerella forsythia, and Aggregatibacter actinomycetemcomitans—plays a pivotal role in the initiation and progression of periodontitis. As for peri-implantitis, alterations include a higher abundance of opportunistic pathogens and reduced microbial diversity around implants. Moreover, oral dysbiosis potentially influencing systemic health through immune-mediated pathways. Regional immunity of periodontium involving neutrophils, T helper cells-17, and immune-related cytokines is crucial for maintaining periodontal homeostasis and responding to microbial imbalances. Additionally, the impact of non-mechanical treatments—such as probiotics and laser therapy—on the oral microbiome is discussed, demonstrating their potential in managing microbial dysbiosis. These findings underscore that bacterial dysbiosis is a central factor in the development of periodontitis and peri-implantitis. Maintaining microbial balance is essential for preventing these diseases, and interventions targeting the microbiome could enhance treatment outcomes. Strategies focusing on controlling pathogenic bacteria, modulating immune responses, and promoting tissue regeneration are key to restoring periodontal stability. Further research is needed to clarify the mechanisms underlying the transition from peri-implant mucositis to peri-implantitis and to optimize prevention and treatment approaches, considering the complex interactions between the microbiome and host immunity.